2021
DOI: 10.1029/2021gl094932
|View full text |Cite
|
Sign up to set email alerts
|

Energy Flux Densities at Dipolarization Fronts

Abstract: Earth's magnetosphere is constantly dynamical during its interaction with the solar wind and involves a global convection cycle of mass, energy and magnetic flux (Dungey, 1961). Such cycle has been suggested to be driven primarily by magnetic reconnection both at regions along the magnetopause (e.g., Burch et al., 2016) and in the magnetotail (e.g., Øieroset et al., 2001). Magnetic reconnection, during which magnetic field lines "break" and "reconnect," has been thought to be capable of efficiently converting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 70 publications
(116 reference statements)
0
11
0
Order By: Relevance
“…The unusual direction of FR2's axis implicates that it may be related to 3D turbulent magnetic reconnection during which axis directions of kinetic‐scale flux ropes could be significantly distorted (e.g., Lapenta et al., 2015). Considering the local decrease in B X and |B|, one can infer that such structure cannot be identified as a magnetic hole (MH) (Liu, Fu, Yu, et al., 2021), because: (a) electron flow vortex, which is typically generated due to magnetic field gradient at MH boundaries, was not observed; (b) the MH model cannot explain the observed bipolar variation of the magnetic field B Y . Note that both the ropes are associated with density increase (Figure 1f) and energetic particle flux enhancement (Figures 1h and 1i), indicating particle acceleration therein, consistent with previous studies suggesting that flux ropes are efficient particle accelerators (e.g., Drake, Swisdak, Che, & Shay, 2006; Wang et al., 2010).…”
Section: Observationmentioning
confidence: 99%
“…The unusual direction of FR2's axis implicates that it may be related to 3D turbulent magnetic reconnection during which axis directions of kinetic‐scale flux ropes could be significantly distorted (e.g., Lapenta et al., 2015). Considering the local decrease in B X and |B|, one can infer that such structure cannot be identified as a magnetic hole (MH) (Liu, Fu, Yu, et al., 2021), because: (a) electron flow vortex, which is typically generated due to magnetic field gradient at MH boundaries, was not observed; (b) the MH model cannot explain the observed bipolar variation of the magnetic field B Y . Note that both the ropes are associated with density increase (Figure 1f) and energetic particle flux enhancement (Figures 1h and 1i), indicating particle acceleration therein, consistent with previous studies suggesting that flux ropes are efficient particle accelerators (e.g., Drake, Swisdak, Che, & Shay, 2006; Wang et al., 2010).…”
Section: Observationmentioning
confidence: 99%
“…We calculate the energy flux densities by a standard decomposition approach which treats the particle population as a single distribution (e.g., Eastwood et al., 2020; Goldman et al., 2016; Liu, Fu, Yu, et al., 2021). The energy fluxes are calculated as: Ks=12nsmsus2us ${\boldsymbol{K}}_{\mathbf{s}}=\frac{1}{2}{n}_{\mathrm{s}}{m}_{\mathrm{s}}{u}_{\mathrm{s}}^{2}{\boldsymbol{u}}_{\mathbf{s}}$ Hs=usTr()Pstrue→2+us·truePnormals ${\boldsymbol{H}}_{\mathbf{s}}=\frac{{\boldsymbol{u}}_{\mathrm{s}}Tr\left(\overrightarrow{{P}_{\mathrm{s}}}\right)}{2}+{\boldsymbol{u}}_{\mathrm{s}}\cdot \stackrel{{\leftrightarrow}}{{P}_{\mathrm{s}}}$ S=E×B/μ0 $\boldsymbol{S}=\boldsymbol{E}\times \boldsymbol{B}/{\mu }_{0}$ where Ks ${\boldsymbol{K}}_{\mathrm{s}}$, ns ${n}_{\mathrm{s}}$, ms ${m}_{\mathrm{s}}$, us ${\boldsymbol{u}}_{\mathrm{s}}$, Hs ${\boldsymbol{H}}_{\mathrm{s}}$, …”
Section: Methodsmentioning
confidence: 99%
“…Energy conversion at DFs are attributable to intense currents and electric fields developed during the interaction between DFs and ambient plasmas (e.g., Fu et al., 2020; Huang et al., 2015; Khotyaintsev et al., 2017; Liu, Fu, Vaivads, et al., 2018, Liu, Fu, Xu, et al., 2018; Yao et al., 2017), and are manifested by various energy channels, such as local particle heating and acceleration (e.g., Bai et al., 2022; Birn et al., 2013, Fu, Khotyaintsev, Vaivads, et al., 2012; Fu et al., 2011; Gabrielse et al., 2016; Liu, Fu, Cao, et al., 2017, Liu, Fu, Xu, et al., 2017; Lu et al., 2016, 2020; Xu et al., 2018; Zhou et al., 2013, 2018), wave‐particle interactions (e.g., Divin et al., 2015; Fu et al., 2014; Huang et al., 2012, 2019; Hwang et al., 2014; Khotyaintsev et al., 2011; Liu et al., 2019, Liu, Fu, Liu, & Xu, et al., 2021; Zhou et al., 2009), and transport by wave emissions in a form of Poynting flux (e.g., Liu, Fu, Yu, et al., 2021). Previous statistical studies have revealed that energy conversion at DFs are usually dominated by energy loads (bold-italicE·bold-italicJ>0 $\boldsymbol{E}\cdot \boldsymbol{J} > 0$), that is, energy going from electromagnetic fields to particles (e.g., Huang et al., 2015; Zhong et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such electron-scale ripple structure can be generated by lower hybrid drift instability (Divin et al 2015b;Pan et al 2018). Liu et al (2021c) presented a detailed investigation of energy flux densities at two RFs with/without the electron-scale surface ripples and indicated that surface ripples may play an important role in the particle dynamics. But how such electron-scale RF structure impacts the electron energization and transport still remains unknown.…”
Section: Introductionmentioning
confidence: 99%